International environmental law principles relevant to exploitation activity in the Area. (April 2020) - Warner, Robin
Abstract: The International Seabed Authority is responsible for providing effective protection for the marine environment from the harmful effects of activities in the Area under Article 145 of UNCLOS. To meet this challenge, it must determine the relevant environmental governance principles applicable to each stage of an exploration and exploitation activity and how they can be operationalized in practical terms. This article discusses some key principles of international environmental law and management which are potentially relevant to the exploitation process and in particular the approval of a plan of work for exploitation activities. It also examines the potential legal thresholds for approval or denial of a proposed plan of work for exploitation activity in the Area. Highlights: Environmental law principles and exploitation in the Area. Legal thresholds for approval of exploitation. Incorporation of international environmental law principles into draft exploitation regulations.